Depression, anxiety stress and associated factors among university students in France. (13th November 2019) - Herrmann, K; Déchelotte, P; Ladner, J; Tavolacci, M P
Abstract: Background: Graduate education is associated with many life changes and stressful events for students, potentially causing depression, anxiety and stress. Prevalence of these disorders and potential associated factors are not clearly identified. Methods: A cross-sectional study was conducted among university students in France. The students filled out a self-questionnaire recording depression anxiety and stress with the DASS21. High" and "very High" intensity symptoms were grouped into "presence" of depression, anxiety and stress and "moderate" "light" "normal" were grouped into "absence" of depression, anxiety and stress. Curriculum, perceived academic pressure, financial difficulties, smoking, binge drinking and eating disorders were also recording. Results: A total of 1, 202 students were included of which 17.8% were healthcare students. The sex ratio (M:F) was of 0.42 with a mean age of 20.0 years. Prevalence of depression, anxiety and stress were respectively 16.4%, 26.4% and 16.0%. After multivariate analysis, female gender was associated with presence of stress (AOR=1, 41 IC 95% [1, 03-1, 93]). High level of perceived academic pressure (AOR=2, 13 [1, 61-2, 82], 2, 05 [1, 57-2, 68], 2, 35 [1, 72-3, 22]) financial difficulties (AOR=1, 33 [1, 03-1, 73], 1, 54 [1, 19-1, 99], 1, 37 [1, 04-1, 82]) and eating disorders (AOR=2, 46 [1, 83-3, 31], 2, 36 [1, 75-3, 19], 2, 21 [1, 63-23]) were associated with presence of depression, anxiety and stress. Binge drinking (AOR=1, 48 [1, 05-2, 09]) and smoking (AOR=1, 46 [1, 01-2, 13]) were associated with anxiety. Conclusions: These results show prevalence of depressive, anxiety and stress symptoms among students. Poor mental health is related to academic and financial difficulties, and is associated especially with eating disorders. There is a pressing need to prioritize mental health of college students through the national public health policies. Additional studies are needed to better understand the relationships between these different factors. Key messages: There is a significant prevalence of depression, anxiety and stress symptoms among Rouen students. Depression, anxiety and stress symptoms among students are associated with high level of perceived academic pressure, financial difficulties and presence of eating disorders.